Analisis Pengaruh Ease of Use dan Perceived Security terhadap User Satisfaction melalui User Trust pada Aplikasi Mobile Banking BCA - Hanif Naufal Rafii; Umi Widyastuti; Terrylina Arvinta Monoarfa (PENG: Jurnal Ekonomi dan Manajemen, 2026)
This study aims to explain the influence of ease of use and perceived security on user satisfaction, with user trust as a mediating variable, in the use of the BCA Mobile banking application. The research employed a quantitative approach using an associative method. Data were collected through questionnaires distributed to respondents who are active users of BCA Mobile and reside in the Jakarta area. The sampling technique used was non-probability sampling with a purposive sampling approach. A total of 112 respondents were analyzed. Data processing was conducted using SmartPLS version 4.0. The analytical techniques included outer model testing, inner model testing, path analysis, t-test, and mediation analysis using the bootstrapping method. The results of the study indicate that: (1) Ease of Use has a positive and significant effect on User Trust; (2) Perceived Security has a positive and significant effect on User Trust; (3) Ease of Use has a positive and significant effect on User Satisfaction; (4) Perceived Security has a positive and significant effect on User Satisfaction; and (5) User Trust has a positive and significant effect on User Satisfaction.